FIRM SIZE MEMODERASI CORPORATE SOCIAL RESPONSIBILITY DAN GOOD CORPORATE GOVERNANCE PADA NILAI PERUSAHAAN - Rahman Sastrawan; Ariefanda Iqbal Perdhana; Chornolius Hendreo (JURNAL LENTERA AKUNTANSI, 2022)
The establishment of a company can advance the economy and improve people's welfare. However, companies are also required to be able to increase the welfare of shareholders by increasing the value of the company. There are several factors that influence company value, namely corporate social responsibility (CSR) and good corporate governance (GCG). This study aims to see how much influence CSR and GCG have on company value, while firm size is a moderating variable for companies registered at CGPI for the 2017-2021 implementation period. This study uses the method of clarity (explanation) with secondary data (financial reports and CGPI data). Hypothesis testing uses the WarpPLS application with the Structural Equation Modeling (SEM) approach. The results of the study show that CSR carried out by companies does not have a significant impact on firm value even though it is reinforced by firm size, while GCG influences firm value by strengthening firm size. This research is useful as a research reference in the field of accounting, as well as providing information in making investment decisions in a company.Key words: Corporate Social Responsibility, Good Corporate Governance, Company Size, Company